2018
DOI: 10.1111/acv.12434
|View full text |Cite
|
Sign up to set email alerts
|

The role of immigration and reinforcement in the population dynamics of a long‐lived bird: implications for the conservation of threatened species

Abstract: Understanding population dynamics requires knowledge of the differential effects of survival, productivity and dispersal on population growth. This is particularly important for the conservation of small and recently established populations, where stochastic births and deaths may result in negative growth and even extinction. Here, we investigated the population dynamics of a small population of Eurasian cranes Grus grus in the UK and the effect of a population reinforcement in population growth. We also estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
(65 reference statements)
0
12
1
Order By: Relevance
“…For instance, Serrano et al (2021) showed that natal dispersal distances of Egyptian vultures were negatively related to natal breeding population density and population trends (social cues). Hence, increasing the breeding success with low adult mortality rate, as our case (Zuberogoitia et al, 2009), would help to increase the viability of Egyptian vulture populations, not only in the target area but also in the neighboring regions since they play an essential role in demographic processes such as source-sink dynamics (e.g., Hernández-Matias et al, 2013;Lieury et al, 2016;Weegman et al, 2016;Sanz-Aguilar et al, 2017;Soriano-Redondo et al, 2019). Conservation programs that succeed in reducing and palliating the main threats to target species and identify and engage with all stakeholders to implement solutions, particularly in areas of conflict with high human density, should be regarded effective.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, Serrano et al (2021) showed that natal dispersal distances of Egyptian vultures were negatively related to natal breeding population density and population trends (social cues). Hence, increasing the breeding success with low adult mortality rate, as our case (Zuberogoitia et al, 2009), would help to increase the viability of Egyptian vulture populations, not only in the target area but also in the neighboring regions since they play an essential role in demographic processes such as source-sink dynamics (e.g., Hernández-Matias et al, 2013;Lieury et al, 2016;Weegman et al, 2016;Sanz-Aguilar et al, 2017;Soriano-Redondo et al, 2019). Conservation programs that succeed in reducing and palliating the main threats to target species and identify and engage with all stakeholders to implement solutions, particularly in areas of conflict with high human density, should be regarded effective.…”
Section: Discussionmentioning
confidence: 82%
“…The number of birds in each age class was estimated for each year by random binomial draws with the survival probability of birds from the previous year. Although immigration can be an important driver of population dynamics in small populations (Lieury et al., 2015; Schaub & Ullrich, 2021; Soriano‐Redondo et al., 2019), and has been shown for other raptors in the Balkans (Demerdzhiev et al., 2015), we did not include an immigration component in our population model. The Egyptian Vulture population in the Balkans is small and fragmented (Velevski et al., 2015), and >500 km from the nearest healthy source population that could provide a significant number of immigrants (Balaban & Yamac, 2018; Katzenberger et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Sergio et al 2011). After visualizing survival estimates from a model with age in years as a factor (0-9 years), we collated the data into 10 different age-class groupings based on various fledgling, subadult and adult classes (Mathews & Macdonald 2001, Soriano-Redondo et al 2019a) and ran models testing the effect of the groupings on survival, with constant encounter probability. Models were ranked using Akaike's Information Criterion adjusted for small sample size (AICc; Burnham & Anderson 2002) and the age structure in the top model was selected for use in subsequent models.…”
Section: Survivalmentioning
confidence: 99%
“…However, largely as a result of overexploitation, Common Cranes were extirpated in the UK in the 17th century (Mathews & Macdonald 2001, Stanbury 2011. In 1979, a pair naturally re-established in Norfolk, east England, and by 2015, this population had increased to 20 breeding pairs (Soriano-Redondo et al 2019a). Being a long-lived species with slow maturity, expansion of this population was likely to continue to be slow without active intervention.…”
mentioning
confidence: 99%